Evaluation of the Bond Strength on One Bottle Adhesive to Deciduous Teeth - Sofia Takeda UEMURA; Carolina Cardoso GUEDES; Kristianne Porta S. FERNANDES; Manoela Domingues MARTINS; Sandra Kalil BUSSADORI (Association of Support to Oral Health Research (APESB), 2006)
Objective:This study was carried out with the purpose to evaluate through traction test the bond strength of four one bottle adhesive systems to decidous teeth dentine. Method: For this experiment twenty temporary molar teeth were used from the Human Teeth Bank in the Faculty of Dentistry at the University of Sao Paulo. All teeth were cut in the mesion-distal direction and included in light-cured acrylic resin with its vestibular, palatal and lingual faces directed toward the external surface. The teeth had its vestibular and lingual faces worn till the areas were all flat and randomly divided into four groups. G1: Prime & Bond NT (Dentsply Caulk); G2: Optbond Solo (Kerr); G3: Excite (Vivadent) and G4: Single Bond (3M). The adhesive systems were applied according to the manufactures instructions. The same restorative material (Filtek Z-250 3M) was used in all groups. The samples were conserved in distilled during 24h and then submerged in traction assay. Results: Groups 2 and 3 brings the lowest notes and groups 1 and 4 the highest notes. Conclusion: In the conditions of this study the adhesive system Single Bond (3M) and Prime & Bond NT (Dentsply Caulk) presented better bond strength resistance to the deciduous teeth dentine.